FEATURES OF THE FOUR-LEVEL APPROACH TO TRAINING FOR STUDENT OLYMPIADS IN COMPUTER SCIENCE - Vapnichnyi, S. (Zhytomyr Ivan Franko State University Journal Рedagogical Sciences, 2022)
The article proposes elements of the methodological system of training students for computer science Olympiads (CSO), which covers four levels: basic, medium, high and advanced. For each of the levels, a list of topics is given; for some topics there are proposed assessment tasks, that can be used to determine the student's readiness. Also for each level the sets of tasks on eolymp.com and codeforces.com are offered. To increase the effectiveness of the proposed approach, it is recommended that students, starting from the medium level, participate in various competitions and Olympiads, which give many motivating impulses to master programming. High and advanced levels include own topics and tasks as well. Besides, the paper formulates the requirements that were the basis for the selection of tasks by topics and separation of the proposed levels. In particular, there are proposed the following requirements for tasks: availability of interesting plot, making curiosity for students, illustrativeness, connectivity and diversity. The construction of task systems takes into account the didactic and methodological requirements that determine the pedagogical expediency of their use. The model of the process of creating a tasks system, which consists of analytical, design and technological stages, is described. The proposed approach methodology was successfully used in teaching students of Uzhhorod specialized boarding school with in-depth study of certain subjects (UzhSBSwiDSCS), at summer and winter programming schools in Kremenchug and summer programming schools in Khust. Many students of UzhSBSwiDSCS studied on the basis of this approach, participated in competitions and became winners of various stages of the All-Ukrainian Student Olympiad in Informatics. The mentioned approach has been successfully tested in distance learning.